TRANSMISI TRANSOVARIAL VIRUS DENGUE PADA NYAMUKAEDES SPP. - Sorisi, Angle M. H. (JURNAL BIOMEDIK : JBM, 2013)
Abstract: Dengue Hemorrhagic Fever (DHF) is one of the most serious health problems in Indonesia which often causes outbreaks with numerous deaths. The disease is transmitted byAedes sp.females. Generally, dengue virus transmission occurs horizontally from human carriers, and the dengue viruses are passed on bytheir vectors through blood sucking activity. After propagation in the mosquito, the viruses are transmitted to human recipients. In addition, there is a vertical transmission (transovarial) of dengue virusesin the ova of Aedes sp.females. The viruses propagate in the ova that undergo  metamorphosis to become larvae, pupae, and imagoes. The transovarial transmission of dengue virusesin its vectors in endemic areas could be a causative key which is responsible for the phenomenon of increasing cases of DHF. Any effort to prevent and control DHF requires a thorough understanding about virDen transmission, including this transovarial transmission in Aedes spfemales. Keywords: DHF, transovarial transmission, Aedes sp.     Abstrak: Penyakit Demam Berdarah Dengue (DBD) merupakan salah satu masalah kesehatan yang semakin serius di Indonesia dan sering menimbulkan suatu Kejadian Luar Biasa (KLB) dengan jumlah kematian tinggi. Penyakit ditularkan melalui Aedes sp.betina. Transmisi virus dengue umumnya terjadi secara horizontal, yaitu dari manusia pembawa virus dengue ke nyamuk vektor Aedes sp. melalui aktivitasnya mengisap darahSetelah mengalami propagasi  dalam  tubuh nyamuk, virus dengue ditularkan ke  manusia penerima. Selain itu, transmisi virus dapat terjadi secara vertikal (transovarial) yaitu virus dengue dalam tubuh nyamuk vektorAedes sp. betinake ovum, kemudian berpropagasi dalam ovum, larva, pupa, dan imago. Transmisi transovarial virus dengueke vektornya di daerah endemik bisa menjadi kunci penyebab yang bertanggung jawab terhadap fenomena peningkatan kasus deman berdarah dengue. Upaya pencegahan dan penanggulangan DBD memerlukan pengetahuan yang matang tentang adanya infeksi transovarial virDen pada nyamuk Aedes sp. Kata kunci : DBD, transmisi transovarial,  Aedes sp.